A fractographic study of clinically retrieved zirconia–ceramic and metal–ceramic fixed dental prostheses. Issue 10 (October 2015) - Pang, Zhen; Chughtai, Asima; Sailer, Irena; Zhang, Yu
Highlights Veneer chipping was the prominent fracture mode in clinically retrieved zirconia–ceramic and metal–ceramic fixed dental prostheses. All fracture initiated at the occlusal wear facets. Zirconia–ceramic exhibited a higher rate of veneer fracture with larger chip sizes relative to their metal–ceramic counterparts.